Nature-Based Solutions for Climate-Resilient Stormwater Management in Jakarta: A Comparative Modeling of Green Roof and Permeable Pavement Performance - Anies Fatmawati; Grace Olivia Silalahi; Fitriyanti Fitriyanti; Mary-Jane Wood (Natural Sciences Engineering and Technology Journal, 2025)
Rapid urbanization and projected climate change impacts pose severe challenges to stormwater management in tropical megacities like Jakarta, Indonesia. Nature-Based Solutions (NBS) are critical for enhancing urban resilience, yet quantitative, context-specific performance data under future climate scenarios are scarce. This study provides a comprehensive, model-based comparative analysis of green roofs and permeable pavements for managing urban stormwater in Jakarta. An archetypal 1-hectare, medium-density urban catchment was developed in the Storm Water Management Model (SWMM). The model was rigorously calibrated and validated against published empirical data from analogous tropical regions (Nash-Sutcliffe Efficiency > 0.78). We evaluated the hydrological (runoff volume, peak flow) and water quality (TSS, TN) performance of green roofs and permeable pavements under partial and full implementation scenarios (25%, 50%, 75%, 100%) for current and two future climate scenarios (RCP4.5, RCP8.5 for 2050). Permeable pavements consistently demonstrated superior hydrological control, achieving up to 82% runoff volume reduction and 88% peak flow attenuation under full implementation for a 2-year baseline storm. Green roofs achieved 48% and 55%, respectively. Under an extreme 25-year storm in the RCP8.5 scenario, performance diminished but remained substantial, with permeable pavements (100% implementation) reducing runoff by 68%. Green roofs provided more consistent pollutant removal, particularly for total nitrogen (approx. 52% removal across scenarios), due to biological processes. In conclusion, both NBS technologies significantly enhance stormwater management capacity, though a clear trade-off exists between the superior hydrological control of permeable pavements and the balanced performance and co-benefits of green roofs. These findings provide a quantitative basis for integrating NBS into urban planning policy in Indonesia to foster climate-adaptive and resilient cities.